Metodología para la aplicación de economía circular y logística inversa en el algodón para la industria textil en Bogotá. (2022)
The global environmental problem is forcing the industrial sectors to opt for solutions for the reduction and elimination of waste produced and derived from each of the activities they carry out, the proposed methodology seeks to support the initiatives of environmental responsibility and also the economic benefit for each of the actors involved, in what would be the strategies of circular economy and reverse logistics applied to the textile sector in Bogotá. The purpose of the methodology is to identify the state of the textile sector against the economic, political, legal, social, technological and environmental opportunities existing in the country, with the objective that these are taken in a strategic way to obtain factors that will define the operation of the processes involved in circular economy practices and reverse logistics for the recovery of cotton from post-consumer garments. There is a great opportunity in the textile sector, due to the amount of waste that is generates and therefore environmental pollution, the methodology is proposed in such a way that it is applicable for those who decide to adopt the strategies of the same, since the recovery process of cotton is directly linked to the traditional process, which facilitates a possible implementation, In addition, recommendations and strategies are provided for optimal execution in each of the aspects to deal with.